THE PRAGMATIC REALIZATION OF COMPUTER TERMINOLOGY IN ENGLISH AND UZBEK: A COMMUNICATIVE AND FUNCTIONAL ANALYSIS OF ANTHROPOMORPHIC, NATUROMORPHIC, AND ARTIFACT METAPHORS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The rapid development of information technologies has significantly expanded the scope and functions of computer terminology in modern languages. This study investigates the pragmatic realization of computer terms in English and Uzbek, focusing on the communicative and functional role of anthropomorphic, naturomorphic, and artifact metaphors. The research is based on a comparative analysis of computer terms collected from technological dictionaries, software interfaces, digital platforms, and professional discourse. Particular attention is paid to the pragmatic mechanisms that facilitate the perception and interpretation of technical concepts by users. The findings reveal that metaphorical computer terms contribute to communicative efficiency by transforming complex technological processes into cognitively accessible concepts. Anthropomorphic metaphors conceptualize technological systems through human characteristics, naturomorphic metaphors rely on natural phenomena, whereas artifact metaphors are based on everyday objects familiar to users. The comparative analysis demonstrates that English and Uzbek computer terminology share common cognitive models while exhibiting language-specific pragmatic adaptations. The study contributes to contemporary terminology theory, cognitive linguistics, and pragmatics by explaining how metaphorical mechanisms enhance the communicative effectiveness of computer discourse.